Cumacés de profondeur de l'atlantique nord-famille des lampropidae - Reyss, Daniel (E. J. Brill, Leiden, 1978)
Deep-sea cumaceans of the farmily Lampropidae are recorded from the North Atlantic Ocean. They belong to the genera Chalarostylis ( 1 species) , Hemilamprops ( 3 species) , Typolamprops (a new genus with 1 new species), Mesolamprops (with 1 new species), Bathylamprops (with 1 new species), Paralamprops (5 species of which 3 new), and Platysympus (1 species). [NOT CONTROLLED OCR]